Institutional protection of minority employees and entrepreneurship: Evidence from the LGBT Employment Non‐Discrimination Acts - Conti, Raffaele; Kacperczyk, Olenka; Valentini, Giovanni (Strategic Management Journal, 2022)
Research Abstract A diverse workforce has long been associated with multiple firm benefits, but this is sometimes difficult to achieve due to employer discrimination. Although multiple institutional arrangements have been put in place to ban discriminatory behavior, the effects of such regulations remain relatively unexplored, often neglecting start‐ups. We propose that institutional changes aiming to outlaw employment discrimination will trigger two main effects: they will (a) depress start‐up founding rates through enhancement of wage‐work appeal, and (b) increase the average start‐up quality due to a higher threshold for leaving wage‐work. We test our predictions by exploiting the staggered enactment of Employment Non‐Discrimination Acts in the U.S. Consistent with our theory, we find that this institutional protection reduced the quantity of entrepreneurship but increased its quality. Managerial Summary Do laws that protect traditionally oppressed groups from discrimination in the workplace affect the propensity of workers to leave their company and start an entrepreneurial venture? Our study shows that legislative changes that ban the discrimination against members of the LGBT community in the labor market have a two‐fold effect on entrepreneurship. First, they reduce the workers' propensity to start a new venture (thus reducing the loss of human capital) because of an increased relative appeal of the workplace. Second, they increase the overall quality of the startups founded in the region, increasing the overall welfare. Additionally, we find that these effects are more likely to be present when litigation against employment discrimination is more frequent and when the protected minorities are more prevalent.